Experimental investigation of flow boiling heat transfer and pressure drops characteristic of R1234ze(E), R600a, and a mixture of R1234ze(E)/R32 in a horizontal smooth tube. (23rd September 2015) - Qiu, Jinyou; Zhang, Hua; Yu, Xiaoming; Qi, Yingxia; Lou, Jiangfeng; Wang, Xi
The saturated flow boiling heat transfer coefficients and frictional pressure drops characteristics of R1234ze(E), R600a, and L-41b (R1234ze(E)/R32 (27/73 mass %)) inside an 8 mm inner diameter horizontal tube were investigated. The experiment was carried out at the saturation temperature of 20°C with heat flux ranging from 5.0 to 10.0 kW·m −2 and mass flux ranging from 200 to 400 kg·m −2 ·s −1 . The influence of mass flux, heat flux, and quality on the heat transfer coefficients and frictional pressure drops were examined and discussed. The results show that the local heat transfer coefficients of R1234ze(E) are averagely 33% and 18% lower than those of R600a and L-41b, respectively. The frictional pressure drops of R1234ze(E) are 21% lower than those of R600a but 6% greater than those of L-41b. Meanwhile, the experimental data of local heat transfer coefficients and frictional pressure drops are compared with some well-known correlations available in literatures.